Breaks in the Variability and Comovement of G-7 Economic Growth - Doyle, Brian M.; Faust, Jon (The Review of Economics and Statistics, 2005)
This paper investigates breaks in the variability and comovement of output, consumption, and investment in the G-7 economies. In contrast with most other papers on comovement, we test for changes in comovement, allowing for breaks in mean and variance. Despite claims that rising integration among these economies has increased output correlations among them, we find no clear evidence of an increase in correlation of growth rates of output, consumption, or investment. This finding is true even for the United States and Canada, which have seen a tremendous increase in bilateral trade shares, and for the euro-area members of the G-7.